2001
DOI: 10.1021/ja003198w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substituting a OH Group by a F Atom in d-Glucose. Ab Initio and DFT Analysis

Abstract: High-level ab initio and DFT methods up to MP2/6-311++G//B3LYP/6-31G and B3LYP/6-311++G//B3LYP/6-31G levels have been used to assess the relative energies of 17 different structures of D-glucose and 13 different structures of 4-deoxy-4-fluoro-D-glucose. The structures were confirmed to correspond to minima on the potential energy surface at the RHF/6-31G level. Solvation Model 5.4/AM1 was used to calculate the effects of aqueous solution. The substitution of a OH group by a F atom does not much change the shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 98 publications
(202 reference statements)
3
57
1
Order By: Relevance
“…Proper selection of the protein domain is necessary [102][103][104][105][106][107][108]. In addition to pure chemical data [109][110][111][112][113][114][115][116] in the context of the Drug Discovery [117][118][119][120][121][122][123][124][125][126][127], there is also a need for some knowledge on protein-protein interactions, the high quality structural prediction of proteins [2,[128][129][130][131][132][133][134][135][136] and their inhibitors, and a detailed understanding of how those inhibitors affect the molecular recognition between proteins. The development of theoretical methods for function annotation clearly shows that a detailed analysis of local characteristics of the protein chain can significantly improve accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Proper selection of the protein domain is necessary [102][103][104][105][106][107][108]. In addition to pure chemical data [109][110][111][112][113][114][115][116] in the context of the Drug Discovery [117][118][119][120][121][122][123][124][125][126][127], there is also a need for some knowledge on protein-protein interactions, the high quality structural prediction of proteins [2,[128][129][130][131][132][133][134][135][136] and their inhibitors, and a detailed understanding of how those inhibitors affect the molecular recognition between proteins. The development of theoretical methods for function annotation clearly shows that a detailed analysis of local characteristics of the protein chain can significantly improve accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution of the C4-OH with -F at the equatorial and axial positions did not significantly influence the interaction with hSGLT3, because the kinetics of 4D4Fglc Ϸ glucose, and neither 4D4Fgal nor galactose interacts with hSGLT3 (Table 1). The ability of -F to mimic the -OH at C4 may be the result of hydrogen bonding; however, recent evidence suggests organic -F is unlikely to participate in hydrogen bonds (Hoffmann and Rychlewski, 2001;Park et al, 2001;Biffinger et al, 2004;Dunitz, 2004). A possibility is the displacement of water molecules interacting with hSGLT3, which -F would do equally well as -OH.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the structural analysis of D-glucose requires the consideration of intramolecular hydrogen bond networks involving adjacent OH groups. The orientation of the hydroxyl groups is relevant to distinguish between the different conformers of D-glucose and is thought to account for Apart from the number of theoretical studies on D-glucopyranose [257,258], only one vibrational spectroscopic study of α-D-glucopyranose isolated in Ar matrix has been reported [259]. Laser spectroscopy through UV-UV and IR-UV doubleresonance techniques has contributed to the description of the conformations of some β-phenylglucopyranosides and their hydrates [219,220,260,261] but these studies are limited to vibrational resolution and the structural conclusions are not totally transferable to D-glucose because of the electronic chromophore at the anomeric position.…”
Section: -Deoxy-d-ribose and Ribosementioning
confidence: 99%